Numerical evaluation of methanol synthesis in catalytic wall-coated microreactors: scale-up and performance analysis of planar and monolithic designs - Silva, João Lameu da; Santana, Harrson Silva; Hodapp, Maximilian Joachim (Frontiers in Chemical Engineering, 2024)
Methanol is one of the most important primary chemical compounds, being an interesting alternative for portable energy applications, also acting as a molecular platform for the synthesis of a wide range of commodities and high added value products. Traditionally, methanol is obtained by catalytic hydrogenation using synthesis gas (CO/CO2/H2) in fixed beds reactors (FBR), which require large reaction volumes and are limited by heat and mass transfer. Wall-coated microreactor technology (MRT) offers a promising alternative to traditional fixed bed reactors. Despite their potential, industrial-scale adoption of microreactors faces challenges related to scale-up. This article aimed to assess methanol synthesis in wall-coated microreactors (planar -MRP and monolithic -MRM) through numerical performance evaluation, using a fixed bed reactor as a reference. A pre-analysis of carbon conversion into methanol from experimental data provided insightful conclusions about recommended operating parameters, suggested as 50 bar, 250 ºC, CO2 ratio of 0.3-0.4, Gas Hourly Space Velocity (GHSV) of 6000-8000 mL/g.h, and stoichiometric hydrogen/carbon ratio about 2-4. The numerical model, coupling chemical kinetics into fluid dynamics, demonstrated good agreement with experimental data. Subsequently, a Design of Experiments identified optimal operating conditions for methanol synthesis (250 ºC, 50 bar, CO2 ratio = 0.32, GHSV = 7595 mL/g.h, hydrogen/carbon ratio = 2.4) in a FBR. MRP and MRM presented equivalent performance with the FBR after adjusting the surface catalytic loading. Especially the MRP showed a potential feature for scale-up, due to the reduced pressure drop. A reactor block with 10 parallelized channels was designed and evaluated by ranging GHSV between 5000 -50000 mL/g.h and surface catalytic loading from 0.04 to 0.12 kg/m 2 . Despite the formation of recirculation zones in conical region, the flow distribution remained satisfactory, ensuring virtually uniform methanol production among units, providing an increase in operational flow, maintaining the microscale efficiency with relatively low pressure drop. The present paper provided a comprehensive analysis of the fundamental interplay between kinetic effects, mass transfer phenomena and reactor design in methanol synthesis applying MRT concepts, offering important insights for performance optimization and scale-up of wall-coated microreactors.